Application of beryllium oxide in slurry development

By introducing beryllium oxide as a carrier material in the slurry, and combining specific glass powder and additives to optimize the ratio and preparation process, the problems of insufficient stability and poor high-pressure resistance of traditional slurry are solved, and the stability and corrosion resistance of electronic devices are significantly improved.

CN119707302AActive Publication Date: 2025-03-28XIAN TENGXING ELECTRONIC TECH CO LTD

Patent Information

Application Number
CN202510227966.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

In some application scenarios, traditional slurries have problems such as insufficient stability and poor high-voltage resistance, which limits the improvement of electronic devices' performance.

Method used

Beryllium oxide is used as the carrier material and combined with specific glass powder and additives, the stability and corrosion resistance of the slurry are improved by optimizing the ratio and preparation process.

Benefits of technology

It significantly improves the stability and corrosion resistance of the slurry, so that electronic devices can maintain stable performance under extreme conditions such as high temperature and high pressure, and resist the corrosion of corrosive substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of slurry, and relates to application of beryllium oxide in slurry development. The invention provides application of beryllium oxide in slurry development, the slurry comprises glass powder and a carrier, and a preparation method of the carrier comprises the following steps: mixing beryllium oxide and an additive according to a mass ratio of 1: (1.5-2), and blending in a mixer for 2-6 hours to obtain the carrier; the additive is prepared from polyamide, isooctyl alcohol, polydimethylsiloxane and terpilenol. Due to the interaction and synergistic effect of the components, the slurry can still keep stable performance under extreme conditions, and can resist corrosion of corrosive substances, so that the stability and reliability of electronic devices are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of slurry and relates to the application of beryllium oxide in slurry development. Background Art

[0002] In the field of electronic device manufacturing, the performance of slurry has a crucial impact on the quality and stability of electronic devices. Slurry is usually used to fill, encapsulate and connect various components in electronic devices, and its stability directly determines the reliability and service life of electronic devices. Traditional slurries have problems such as insufficient stability in certain application scenarios, which limits the improvement of electronic device performance.

[0003] In the prior art, glass powder, as one of the main components of the slurry, is usually composed of a variety of inorganic oxides. These components are obtained through a specific ratio and melting process to obtain glass powder, but different components and preparation processes have a significant impact on the performance of the slurry. At the same time, as another important component in the slurry, the type and preparation method of the carrier are also directly related to the stability of the slurry. Although traditional carrier materials such as alumina and silica can meet the basic needs of the slurry to a certain extent, their performance will be limited under certain specific conditions (such as high-pressure environments). In the preparation process of the carrier material, the selection and ratio of different additives will also have a significant impact on the performance of the carrier material. If the additives are improperly selected or the ratio is unreasonable, it will not only reduce the performance of the carrier material, but also have a negative impact on the overall performance of the slurry.

[0004] Therefore, it is necessary to improve the formulation and preparation process of the slurry to improve its stability. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention proposes a slurry preparation scheme with beryllium oxide as the key component. As a high-performance inorganic material, beryllium oxide has excellent physical and chemical properties, such as high melting point, high hardness, good electrical insulation and chemical stability. Introducing beryllium oxide into the slurry as a carrier material and combining it with specific additives can enhance the stability of the slurry.

[0006] To achieve the above object, the technical solution of the present invention is as follows: In a first aspect, the present invention provides an application of beryllium oxide in the development of a slurry, wherein the slurry comprises glass powder and a carrier, wherein: The preparation method of the carrier is: beryllium oxide and an additive are mixed in a mass ratio of 1:1.5-2, and then placed in a mixer and blended for 2-6 hours to obtain the carrier; The additive consists of polyamide, isooctyl alcohol, polydimethylsiloxane and terpineol; The glass powder consists of SiO2, H3BO3, Al2O3, ZnO and SrO.

[0007] Preferably, the slurry comprises 46-52 parts of glass powder and 35-41 parts of carrier in parts by mass.

[0008] Preferably, the additive consists of 0.3-0.5 parts of polyamide, 0.1-0.2 parts of isooctyl alcohol, 0.05-0.1 parts of polydimethylsiloxane and 0.03-0.08 parts of terpineol in parts by mass.

[0009] More preferably, the glass powder consists of 32-36 parts of SiO2, 22-30 parts of H3BO3, 8-10 parts of Al2O3, 1-3 parts of ZnO and 0.5-3 parts of SrO in terms of mass fractions.

[0010] Preferably, the method for preparing the slurry comprises the following steps: 1) Preparation of glass powder S11. After the components of the glass powder are evenly mixed, they are melted at a temperature of 1000-1100°C for 1-2h, quenched with water, and cooled to solidify; S12. The solidified mixture is successively crushed, ball-milled, sieved and dried to obtain a glass powder having a particle size of less than 5 μm; 2) Preparation of the carrier: beryllium oxide and the additive are mixed in a mass ratio of 1:1.5-2, placed in a mixer and blended for 2-6 hours; 3) Preparation of slurry: At a temperature of 50-60° C., the glass powder and the carrier are evenly dispersed by ultrasonic to obtain a slurry.

[0011] In a second aspect, a slurry with good dispersibility is provided, wherein the slurry comprises glass powder and a carrier, wherein: The glass powder consists of SiO2, H3BO3, Al2O3, ZnO and SrO; The preparation method of the carrier is as follows: beryllium oxide and an additive are mixed in a mass ratio of 1:1.5-2, and the mixture is placed in a mixer and blended for 2-6 hours to obtain the carrier; The additive consists of polyamide, isooctyl alcohol, polydimethylsiloxane and terpineol.

[0012] In a third aspect, a slurry with good stability is provided, wherein the slurry comprises glass powder and a carrier, wherein: The glass powder consists of SiO2, H3BO3, Al2O3, ZnO and SrO; The preparation method of the carrier is as follows: beryllium oxide and an additive are mixed in a mass ratio of 1:1.5-2, and the mixture is placed in a mixer and blended for 2-6 hours to obtain the carrier; The additive consists of polyamide, isooctyl alcohol, polydimethylsiloxane and terpineol.

[0013] Preferably, the glass powder consists of 32-36 parts of SiO2, 22-30 parts of H3BO3, 8-10 parts of Al2O3, 1-3 parts of ZnO and 0.5-3 parts of SrO in parts by mass.

[0014] Preferably, the additive consists of 0.3-0.5 parts of polyamide, 0.1-0.2 parts of isooctyl alcohol, 0.05-0.1 parts of polydimethylsiloxane and 0.03-0.08 parts of terpineol in parts by mass.

[0015] In a fourth aspect, there is provided application of the slurry of the present invention in improving the stability of electronic devices.

[0016] A fifth aspect provides application of the slurry of the present invention in improving the high voltage resistance of electronic devices.

[0017] In a sixth aspect, there is provided application of the slurry described in the present invention in improving the corrosion resistance of electronic devices.

[0018] In a seventh aspect, there is provided application of the slurry described in the present invention in improving the thermal stability of electronic devices.

[0019] In the present invention, glass powder, beryllium oxide and additives each play a very important role in improving the stability and corrosion resistance of the slurry. The interaction and synergistic effect between these components enable the slurry to maintain stable performance under extreme conditions such as high temperature and high pressure, and can also resist the erosion of corrosive substances, thereby improving the stability and reliability of electronic devices.

[0020] Regarding stability: On the one hand, the particles of glass powder can fill the gaps in the slurry, increase the density of the slurry, and thus improve its compressive strength. On the other hand, the high melting point of beryllium oxide enables it to maintain structural stability under extremely high temperature conditions and is not easy to melt or deform; at the same time, its high hardness also helps the slurry resist deformation under high pressure. On the other hand, the additive composed of polyamide, isooctyl alcohol, polydimethylsiloxane and pinene alcohol can form a good interface with beryllium oxide, thereby improving the stability of the slurry.

[0021] Regarding corrosion resistance: On the one hand, beryllium oxide can resist the erosion of a variety of chemically corrosive media, and this property enables the slurry to maintain stable performance when in contact with corrosive substances. On the other hand, the additives composed of polyamide, isooctyl alcohol, polydimethylsiloxane and terpineol can form a hydrophobic protective film on the surface of the slurry, which can not only isolate the contact between the corrosive medium and the inside of the slurry, but also reduce the erosion of the corrosive medium.

[0022] Compared with the prior art, the beneficial effects of the present invention are: The slurry of the present invention comprises a specific glass powder and a specific carrier combination, and an optimized preparation process; the carrier of the present invention is composed of beryllium oxide and a specific additive; the combination and preparation method of the present invention enable the slurry to have excellent stability, thereby improving the reliability and service life of the electronic device.

[0023] The present invention obtains glass powder with small particle size and uniform distribution by optimizing the ratio and melting process of glass powder. At the same time, the performance of the carrier is improved by selecting appropriate additives and ratios and optimizing the preparation process of the carrier. Under the combined effect of these measures, the slurry can be evenly dispersed during the preparation process, thereby improving the stability of the slurry. In addition, the introduction of beryllium oxide further enhances the stability of the slurry.

[0024] Specifically, the high melting point and chemical stability of beryllium oxide enable the slurry to maintain stable performance under extreme conditions such as high temperature and high pressure. In addition, the introduction of additives can also enhance the corrosion resistance of the slurry and further improve the stability of electronic devices.

[0025] In summary, the present invention solves the problems of insufficient slurry stability and poor high-voltage resistance in the prior art by introducing beryllium oxide as a key component, combining a specific glass powder and carrier combination and an optimized preparation process, and provides a high-performance slurry preparation solution for the field of electronic device manufacturing. This is mainly due to the coordination of glass powder and carrier, and the synergistic effect of beryllium oxide and additives in the carrier. DETAILED DESCRIPTION

[0026] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0027] The technical scheme of the present invention is described below in conjunction with the examples, but the present invention is not limited to the following examples. The experimental methods and detection methods described in each example are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0028] Example 1 This embodiment provides a slurry, which includes 46 parts of glass powder and 35 parts of carrier in terms of weight. The glass powder is composed of 32 parts of SiO2, 22 parts of H3BO3, 8 parts of Al2O3, 1 part of ZnO and 0.5 part of SrO; The preparation method of the carrier is as follows: beryllium oxide and an additive are mixed in a mass ratio of 1:1.5, and the mixture is placed in a mixer and blended for 2 hours; The additive consists of 0.3 parts of polyamide, 0.1 parts of isooctyl alcohol, 0.05 parts of polydimethylsiloxane and 0.03 parts of terpineol.

[0029] Example 2 This embodiment provides a slurry, which includes 52 parts of glass powder and 41 parts of carrier in terms of weight. The glass powder is composed of 36 parts of SiO2, 30 parts of H3BO3, 10 parts of Al2O3, 3 parts of ZnO and 3 parts of SrO; The preparation method of the carrier is as follows: beryllium oxide and an additive are mixed in a mass ratio of 1:2, and the mixture is placed in a mixer and blended for 6 hours; The additive consists of 0.5 parts of polyamide, 0.2 parts of isooctyl alcohol, 0.1 parts of polydimethylsiloxane and 0.08 parts of terpineol.

[0030] Example 3 This embodiment provides a slurry, which includes 50 parts of glass powder and 40 parts of carrier in terms of weight. The glass powder is composed of 33 parts of SiO2, 26 parts of H3BO3, 9 parts of Al2O3, 2 parts of ZnO and 1 part of SrO; The preparation method of the carrier is as follows: beryllium oxide and an additive are mixed in a mass ratio of 1:2, and the mixture is placed in a mixer and blended for 4 hours; The additive consists of 0.4 parts of polyamide, 0.1 parts of isooctyl alcohol, 0.08 parts of polydimethylsiloxane and 0.05 parts of terpineol.

[0031] Example 4 This embodiment provides a method for preparing a slurry, and the preparation method comprises the following steps: 1) Preparation of glass powder S11. After the components of the glass powder are evenly mixed, they are melted at a temperature of 1000-1100°C for 1-2h, quenched with water, and cooled to solidify; S12. The solidified mixture is successively crushed, ball-milled, sieved and dried to obtain a glass powder having a particle size of less than 5 μm; 2) Preparation of the carrier: beryllium oxide and the additive are mixed in a mass ratio of 1:1.5-2, placed in a mixer and blended for 2-6 hours; 3) Preparation of slurry: At a temperature of 50-60° C., the glass powder and the carrier are evenly dispersed by ultrasonication to obtain a slurry.

[0032] Comparative Example 1 This comparative example is the same as Example 3, except that the polydimethylsiloxane in the additive is replaced by polyvinyl alcohol.

[0033] Comparative Example 2 This comparative example is the same as Example 3, except that the mass ratio of beryllium oxide to the additive is adjusted to 1:1.

[0034] Comparative Example 3 This comparative example is the same as Example 3, except that beryllium oxide is replaced by silicon dioxide.

[0035] Effect verification Experimental objects: slurries prepared in accordance with Example 4 in Examples 1-3 and Comparative Examples 1-3; Experimental methods: The above slurries were respectively screen-printed on 1206-gauge alumina substrates, dried at 150°C for 13 min, and then cured at 200°C for 35 min to prepare samples, and then the performance was tested; Corrosion resistance test: Soak the sample in 20% dilute sulfuric acid solution for 96 hours, tear off the sample with 3M tape, and observe whether it falls off; Thermal stability test: quickly heat the sample to 500°C, then quickly cool it down to observe whether the sample has cracks, deformation or falling off; Breakdown voltage test: Apply gradually increasing voltage to the sample until it breaks down, record the breakdown voltage value, and evaluate the sample's voltage resistance; Experimental results: as shown in Table 1.

[0036] Table 1 Performance test results of each group of samples

[0037] In order to further demonstrate the effect of the present invention, the polyamide, isooctyl alcohol and terpineol in the additives in the examples of the present invention are replaced by other substances with similar properties, and the other conditions are consistent with those in Example 3. It is found that the effect is equivalent to that in Comparative Example 1.

[0038] In order to further demonstrate the effect of the present invention, the mass ratio of beryllium oxide to the additive in the present embodiment is adjusted to 1:2.5, and the other conditions are consistent with those in Example 3. It is found that the effect is equivalent to that in Comparative Example 2.

[0039] As can be seen from Table 1, the performance of each group of samples made of the slurry of the present invention is relatively good. Specifically, with regard to corrosion resistance, the corrosion resistance of each group of samples made of the slurry of the present invention is excellent, and no shedding phenomenon occurs; while the samples of each group of comparative examples 1-3 all have a large amount of shedding phenomenon, which means that they cannot maintain sufficient durability in a corrosive environment. With regard to thermal stability, the thermal stability of each group of samples made of the slurry of the present invention is excellent, and no cracks, deformation, or shedding occurs at 500°C; while the samples of each group of comparative examples 1-3 all have a large degree of deformation and shedding phenomenon. With regard to breakdown voltage, the breakdown voltage of each group of samples of the present invention can reach a relatively high level and is very stable, among which the breakdown voltage value of the sample of Example 3 is the highest; while the breakdown voltage of each group of samples of Comparative Examples 1-3 is relatively low. Therefore, compared with the slurry without the formulation system of the present invention, the slurry using the formulation system of the present invention can be well used for the packaging and protection of various high-performance electronic devices. Among them, the corrosion resistance, thermal stability and high-voltage resistance of the sample of Example 3 are superior.

[0040] Through the effect verification experiment, it can be known that the formula system of the slurry provided by the present invention is a whole. Specifically, the functions of the raw materials in the slurry support each other and there is an interactive relationship. It is precisely because the functions of the raw materials support each other and there is an interactive relationship that the slurry of the formula system of the present invention can be well used for the packaging and protection of various high-performance electronic devices.

[0041] It should be understood that the disclosed invention is not limited only to the specific method, scheme and material of description, because these all can change.It should also be understood that the terminology used herein is only for the purpose of describing specific embodiment scheme, rather than being intended to limit the scope of the present invention, and the scope of the present invention is only limited to the appended claims.

Claims

1. The application of beryllium oxide in slurry development is characterized by: The slurry comprises glass powder and a carrier, wherein: The preparation method of the carrier is: beryllium oxide and an additive are mixed in a mass ratio of 1:1.5-2, and then placed in a mixer and blended for 2-6 hours to obtain the carrier; The additive consists of polyamide, isooctyl alcohol, polydimethylsiloxane and terpineol; The glass powder consists of SiO2, H3BO3, Al2O3, ZnO and SrO.

2. The use according to claim 1, characterized in that: The slurry includes 46-52 parts of glass powder and 35-41 parts of vehicle in terms of weight.

3. The use according to claim 1, characterized in that: Calculated by weight, the additive consists of 0.3-0.5 parts of polyamide, 0.1-0.2 parts of isooctyl alcohol, 0.05-0.1 parts of polydimethylsiloxane and 0.03-0.08 parts of terpineol.

4. The use according to claim 1, characterized in that: Calculated by weight, the glass powder consists of 32-36 parts of SiO2, 22-30 parts of H3BO3, 8-10 parts of Al2O3, 1-3 parts of ZnO and 0.5-3 parts of SrO.

5. The use according to any one of claims 1 to 4, characterized in that: The preparation method of the slurry comprises the following steps: 1) Preparation of glass powder S11. After the components of the glass powder are evenly mixed, they are melted at a temperature of 1000-1100°C for 1-2h, quenched with water, and cooled to solidify; S12. The solidified mixture is successively crushed, ball-milled, sieved and dried to obtain a glass powder having a particle size of less than 5 μm; 2) Preparation of the carrier: beryllium oxide and the additive are mixed in a mass ratio of 1:1.5-2, placed in a mixer and blended for 2-6 hours; 3) Preparation of slurry: At a temperature of 50-60° C., the glass powder and the carrier are evenly dispersed by ultrasonication to obtain a slurry.

6. A slurry with good stability, characterized in that: The slurry comprises glass powder and a carrier, wherein: The glass powder consists of SiO2, H3BO3, Al2O3, ZnO and SrO; The preparation method of the carrier is: beryllium oxide and an additive are mixed in a mass ratio of 1:1.5-2, and then placed in a mixer and blended for 2-6 hours to obtain the carrier; The additive consists of polyamide, isooctyl alcohol, polydimethylsiloxane and terpineol.

7. The slurry according to claim 6, characterized in that Calculated by weight, the glass powder consists of 32-36 parts of SiO2, 22-30 parts of H3BO3, 8-10 parts of Al2O3, 1-3 parts of ZnO and 0.5-3 parts of SrO.

8. The slurry according to claim 6, characterized in that Calculated by weight, the additive consists of 0.3-0.5 parts of polyamide, 0.1-0.2 parts of isooctyl alcohol, 0.05-0.1 parts of polydimethylsiloxane and 0.03-0.08 parts of terpineol.

9. Use of the slurry according to any one of claims 6 to 8 in improving the stability of electronic devices.

10. Use of the slurry according to any one of claims 6 to 8 in improving the corrosion resistance of electronic devices.

Citation Information

Patent Citations

  • High-temperature infrared frequency-modulation dielectric paste and preparation method thereof

    CN106653151A

  • Preparation method of conductive sliver ink

    CN107118620A

  • Copper paste for metallization, glass powder, preparation method and dielectric filter

    CN115274177A

  • Glass powder, preparation method thereof and thick film slurry

    CN117923796A

  • Glass packaging material for lithium thionyl chloride battery and preparation method of glass packaging material

    CN118754446A

Cited By

  • Glass powder for TOPCon high-sheet-resistance battery front-side fine grid slurry suitable for LECO process and preparation method of glass powder for TOPCon high-sheet-resistance battery front-side fine grid slurry

    CN122344089A